2020
DOI: 10.5334/aogh.2804
|View full text |Cite
|
Sign up to set email alerts
|

Graduate Midwifery Education in Uganda Aiming to Improve Maternal and Newborn Health Outcomes

Abstract: Background Maternal and Neonatal MortalityGlobal maternal mortality ratio (MMR) has remained unacceptably high at 216 per 100,000 live births. It is estimated that 830 women die from pregnancy-related complications around the world every day [1]. In low-income countries, one in 16 women dies of complications from pregnancy. In developed countries, the ratio is markedly lower, at one in 2,800 [2].Uganda, situated in East Africa, shoulders a high MMR of 336 per 100,000 live births, largely attributable to hemorr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Firstly, we have to have in mind, that with regard to any potential selection bias and also the limited variation of contexts it seems likely that there are other models existing. As an example, we found a study characterizing the plan of a postgraduate midwifery program at Lira University, Uganda, which is not resembling any of our ve models [22]. The Uganda model is operationalizing critical clinical competences held by masters of midwifery compared to bachelor, improving the likelihood of better clinical outcomes for mother and child.…”
Section: Discussionmentioning
confidence: 93%
“…Firstly, we have to have in mind, that with regard to any potential selection bias and also the limited variation of contexts it seems likely that there are other models existing. As an example, we found a study characterizing the plan of a postgraduate midwifery program at Lira University, Uganda, which is not resembling any of our ve models [22]. The Uganda model is operationalizing critical clinical competences held by masters of midwifery compared to bachelor, improving the likelihood of better clinical outcomes for mother and child.…”
Section: Discussionmentioning
confidence: 93%
“…The extent to which midwives at the University of Port Harcourt Teaching Hospital adhere to ethical standards in their practice is an important and under-explored area of research. The professionalism of midwifery in different countries, such as Belgium, Uganda, and Pakistan, has been studied to understand the state of the profession and identify areas for improvement (Vermeulen et al, 2021;Kumakech et al, 2020;Salman & Al-Fayyadh, 2022). These studies have highlighted the need for unified education programs, recognition of midwives' roles and competencies, and the development of advanced roles in maternity care practice.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Vermeulen et al (2021) found that the achievement of patient-centred care is positively correlated with the extent of adherence to medical ethics among midwives and nurses. Also, Kumakech et al (2020) study which focused on the evaluation of midwifery programs in Uganda showed positive outcomes, with graduates reporting the ability to practice advanced obstetrics and newborn care skills. The development of higher education programs, such as bachelor's and master's degrees in midwifery, has been implemented in different regions to equip midwives with the necessary skills and knowledge for full-scope practice and leadership roles.…”
Section: Introductionmentioning
confidence: 99%
“…One of the established strategies is to improve access to skilled midwifery practitioners and provide adequate health facilities, especially as it could significantly reduce maternal mortality and morbidity [ 9 ]. For example, Uganda has recently upgraded its midwifery education to a Bachelor’s degree, and enabled midwives to employ higher-level skills compared to their certificate-trained counterparts [ 10 ]. To strengthen health systems’ responses to maternal and child health, WHO recommends workforce management with regulated care providers as well as education and core competencies that meet global standards [ 11 ].…”
Section: Introductionmentioning
confidence: 99%